Posture Analysis With REBA And RULA Methods At PT. PAGILARAN Batang Central Java - Muhammad Arul Zaini (Journal of Industrial Engineering and Halal Industries, 2021)
Abstract One of the levels of worker productivity is influenced by work posture. Work posture is an important aspect that needs to be considered in the industrial world, especially in the production process activities. Movement errors that are carried out repeatedly over a long period of time will cause fatigue of musculoskeletal disorders (loading errors on muscles and skeleton) and this can reduce the performance of workers in doing their work. So it is necessary to analyze the work posture of workers or employees using the REBA (Rapid Entire Body Assessment) and RULA (Rapid Upper Limb Assessment) methods which are work posture research methods to investigate disorders of the limbs. Based on the results of data processing using the REBA method, it can be concluded that the work posture in the wet sorting sector has a score of 9. This work posture really needs to be improved and will cause a high impact / risk if it continues. In the results of data processing using the RULA method, the work posture of the milling station workers has a final score of 7. This means that the work posture needs to be improved. The work posture at the two stations to be improved immediately in order to minimize the fatality that occurs in the worker's body posture